Structures and crystal chemistry of the double perovskites Ba2LnB′O6 (Ln=lanthanide and B′=Nb, Ta):. Part II-Temperature dependence of the structures of Ba2LnB′O6 - Saines, P; Spencer, JR; Kennedy, B; Kubota, Y; Minakata, C; Hano, H; Kato, K; Takata, M (2007)
The structures of eight members of the series of double perovskites of the type Ba2LnB′O6 (Ln=La3+-Sm3+ and Y3+ and B′=Nb5+ and Ta5+) were examined both above and below room temperature using synchrotron X-ray powder diffraction. The La3+ and Pr3+ containing compounds had an intermediate rhombohedral phase whereas the other tantalates and niobates studied have a tetragonal intermediate. This difference in symmetry appears to be a consequence of the larger size of the La3+ and Pr3+ cations compared to the other lanthanides. The temperature range over which the intermediate symmetry is stable is reduced in those compounds near the point where the preferred intermediate symmetry changes from tetragonal to rhombohedral. In such compounds the transition to the cubic phase involves higher order terms in the Landau expression. This suggests that in this region the stability of the two intermediate phases is similar. © 2007 Elsevier Inc. All rights reserved.